Direct and Indirect Effects of Atmospheric Carbon Dioxide Enrichment on Leaf Respiration of Glycine max (L.) Merr. - Thomas, R. B. (1994)
Long-term and short-term effects of CO2 enrichment on dark respiration were investigated using soybean (Glycine max [L.] Merr.) plants grown at either 35.5 or 71.0 Pa CO2. Indirect effects, or effects of growth in elevated CO2, were examined using a functional model that partitioned respiration into growth and maintenance components. Direct effects, or immediate effects of a short-term change in CO2, were examined by measuring dark respiration, first, at the CO2 partial pressure at which plants were grown, and second, after equilibration in the reciprocal CO2 partial pressure. The functional component model indicated that the maintenance coefficient of respiration increased 34% with elevated CO2, whereas the growth coefficient was not significantly affected. Changes in maintenance respiration were correlated with a 33% increase in leaf total nonstructural carbohydrate concentration, but leaf nitrogen content of soybean leaves was not affected by CO2 enrichment. Thus, increased maintenance respiration may be a consequence of increased nonstructural carbohydrate accumulation. When whole soybean plants were switched from low CO2 to high CO2 for a brief period, leaf respiration was always reduced. However, this direct effect of CO2 partial pressure was approximately 50% less in plants grown in elevated CO2. We conclude from this study that there are potentially important effects of CO2 enrichment on plant respiration but that the effects are different for plants given a short-term increase in CO2 partial pressure versus plants grown in elevated CO2.